The lines of the head: An analysis of the headlines in a State University newspaper - Gamboa, Jerame; Cayabyab, Melchor (Technium Social Sciences Journal, 2023)
Headlines are important parts of any news and newspaper. They serve as an overview of the story or article. This study aims to describe and analyze the news headlines of the past 5 issues of the school publication in one of the state universities in Region III, Philippines. Specifically, it focuses on the types of grammatical structures are used in the headline writing; patterns that the headlines observe; semantic categories of the headwords of the headlines; reasons why the headlines framed the way they appear in the newspaper; and implications of the results to future journalism training and campus paper publication. The study is a sequential explanatory type of research that used the Fairclough theory to analyze the previous issues of the newspaper. After which, the results were presented to the two (2) advisers of the newspaper who served as the participants during the interview. It was found out that the last five issues of the student publication of a university in the Philippines commonly used clausal headlines, Subject-Verb Phrase-Direct Object clausal pattern, Headword-Postmodifier phrasal headlines, and proper names for the headwords of the headlines. The participants of the study explained that the patterns were adopted for clarity, comprehensiveness, getting the reader’s attention, conciseness, and identification. Therefore, it is recommended that continuous training must be given to the student writers to be able to be abreast of other styles and techniques so that they can present news in a comprehensive, clear, concise, and attractive way.